The Effect Of Facial Vertical Dimension Changes On The Value Of Facial Harmony In Malocclusion Class II Skeletal In RSGM USU: Pengaruh Perubahan Dimensi Vertikal Wajah Terhadap Nilai Harmoni Wajah Pada Maloklusi Kelas II Skeletal di RSGM FKG USU - Yusuf, Muslim; Bahirrah, Siti; Sembiring, Bernadetta (TALENTA, 2020)
Treatment of Class II malocclusion have impact in relation to the vertical dimensions of the skeletal and facial soft tissues mainly to the facial balancing and proportion which relate to patient facial harmony. The aim of this study was to determine the changes and differences in facial vertical dimensions to the total value of facial harmony in skeletal Class II after treatment with extraction and non-extraction of the maxillary first premolar based on Arnett and Bergmann at the Orthodontic Specialist Clinic of RSGM, Universitas Sumatera Utara. The sample consisted of initial and final cephalometry of 36 patients with age 18-35 years old, skeletal Class II malocclusion ANB > 4o, divided into extraction of maxillary first premolar and non-extraction group. Cephalometric tracing with the required points, then the photos are processed into image J software. Then the data that obtained is tested statistically with Pearsonâ€™s Correlation Test and T-Test Independent. There was a significant change between MP-SN and Pog-Imd (P=0,036) in the first premolar extraction group, but there was not a significant change in the non-extraction first premolar group. There was a significant difference in the face harmony value at point G-A between the extraction and non-extraction groups (P=0,038). There was a significant difference on the face harmony value in the treatment of malocclusion Class II orthodontic with maxillary first premolar extraction.Â